2001
DOI: 10.1016/s0014-5793(01)02516-9
|View full text |Cite
|
Sign up to set email alerts
|

LytB, a novel gene of the 2‐C‐methyl‐D‐erythritol 4‐phosphate pathway of isoprenoid biosynthesis in Escherichia coli

Abstract: The mevalonate-independent 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway for isoprenoid biosynthesis is essential in many eubacteria, plants, and the malaria parasite. Using genetically engineered Escherichia coli cells able to utilize exogenously provided mevalonate for isoprenoid biosynthesis by the mevalonate pathway we demonstrate that the lytB gene is involved in the trunk line of the MEP pathway. Cells deleted for the essential lytB gene were viable only if the medium was supplemented with mevalonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
76
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 22 publications
0
76
0
1
Order By: Relevance
“…Comparative genomics suggest that the protein specified by the lytB gene is involved in the conversion of 2C-methyl-D-erythritol 2,4-cyclodiphosphate into IPP and DMAPP (26). Mutagenesis studies confirmed this suggestion (27)(28)(29), but no direct evidence for the specific role of the LytB protein has been reported up to now.…”
mentioning
confidence: 88%
“…Comparative genomics suggest that the protein specified by the lytB gene is involved in the conversion of 2C-methyl-D-erythritol 2,4-cyclodiphosphate into IPP and DMAPP (26). Mutagenesis studies confirmed this suggestion (27)(28)(29), but no direct evidence for the specific role of the LytB protein has been reported up to now.…”
mentioning
confidence: 88%
“…In vivo experiments showed that the reductive ring opening of 7 affording 1-hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate 8 requires a protein specified by the ispG (gcpE) gene (18,19). The same compound was shown also to accumulate in an ispH-deficient Escherichia coli strain (20), and its formation from 14 C-labeled 7 was observed in cell extracts from E. coli overexpressing the ispG (gcpE) gene (21). Subsequent in vivo studies with a recombinant E. coli strain showed that the conversion of 8 into 9 and 10 requires a protein specified by the ispH (lytB) gene (22).…”
Section: Earlier In Vivo Studies Showed the Involvement Of Isph Protementioning
confidence: 99%
“…The additional implementation of a recombinant ispG gene resulted in the in vivo formation of 1-hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate (6) (16), which was also isolated from an ispH-deficient E. coli mutant (17). Subsequently, the in vitro formation of 6 from 5 by crude cell extracts of E. coli overexpressing ispG was confirmed by radiochemical methods (18).…”
mentioning
confidence: 99%